SUPPORTING MILITARY STUDENTS: INSIGHTS FROM THE FRONTLINE - Tarbutton, Tanya; Hill, Samantha (International Online Journal of Education and Teaching, 2025)
This article showcases the challenges military connected students have along their educational journey including; academic, behavioral and emotional barriers. The authors have decades of experience as military spouses, parents and educators and are experts in examining the topic using a lens of authenticity. They suggest using a culturally responsive teaching framework, wrapped in compassionate teaching practices, to better service military connected children. This approach encourages educators to look for and incorporate students' strengths as areas of opportunity and as important assets in a child’s education. Examining military connected students' education through this context helps steward the children of those who serve the country.